Dialogism in publicity discourses of Anglo-American and Chinese universities: A comparative analysis based on Engagement System - Lu Zheng (PLoS ONE, 2026)
Dialogism serves as a critical characteristic of university publicity discourse, encapsulating the origins of ideas and the communicative intentions inherent in such discourse. While both Chinese and Anglo-American university publicity discourses fall under the same category, they exhibit distinct dialogic approaches. To investigate the similarities and differences in dialogism, this study conducts a comparative analysis of dialogic contraction and dialogic expansion within English and Chinese publicity discourses, utilizing the Engagement System developed by functional linguist Martin J.R. The findings indicate that English discourse predominantly articulates its viewpoints through negative constructions to refute alternative perspectives, whereas Chinese discourse asserts its positions firmly with affirmative statements to limit space for opposing views. In terms of dialogic expansion, English discourse allows room for alternative viewpoints when presenting its own stance, while Chinese discourse directly cites other perspectives to bolster its arguments. This study has theoretical and practical significance. Theoretically, it advances Martin’s Engagement System and offers a replicable protocol for cross-cultural discourse studies. Practically, it guides university communications and provides a template for analysts integrating qualitative and quantitative methods.